Photoinduced charge separation in cyclohexylidene-based donor-(σ-Bridge)-acceptor compounds: building blocks for materials - Oosterbaan, Wibren; van Gerven, Paul C. M.; van Walree, Cornelis A.; Koeberg, Mattijs; Piet, Jacob J.; Havenith, Remco W. A.; Zwikker, Jan W.; Jenneskens, Leonardus W.; Gleiter, Rolf (European journal of organic chemistry, 2003)
We describe the syntheses and properties of five semi-rigid donor−(σ-bridge)−acceptor (D−σ−A) compounds. These compounds, which are candidates for incorporation in materials, have aniline-type donors and (mixed) cyano- and alkoxycarbonyl-1,1-difunctionalized vinyl acceptors that are separated by a four-σ-bond bridge. Their electronic properties were studied by means of photoelectron spectroscopy in combination with ab initio MO calculations, cyclic voltammetry, UV-Vis absorption spectroscopy, (time-resolved) fluorescence spectroscopy, and time-resolved microwave conductivity (TRMC). We found that these D−σ−A compounds exhibit a weak intramolecular charge-transfer absorption band that borrows its intensity from local transitions. Upon photoexcitation, a charge-separated state is generated in virtually quantitative yield. Conformational contraction or “folding” of this state takes place for the two D−σ−A compounds with a dicyanovinyl acceptor in apolar solvents. The absence of folding in compounds with an alkoxycarbonyl-functionalized acceptor is attributed to a reduced lifetime of the charge-separated state.
Gesehen am 27.10.2020